Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1002/ijc.2910500526
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of growth of tumours in NC‐cell‐depleted mice with NC‐ and NK‐cell‐mediated lysis in vitro

Abstract: The anti-tumour surveillance activity of natural cytotoxic (NC) cells was studied in vivo using the transplantable tumours WEHI-164 fibrosarcoma, MPC-II plasmacytoma, WEHI-7 T-lymphoma, B16 melanoma and EL-4 thymoma in syngeneic and semi-allogeneic mice. Experimentally, mice were treated with the anti-NC-I.I monoclonal antibody (MAb) IC4 to abrogate splenic NC activity. This was followed by s.c. inoculation of MTD100 doses of the tumours. Comparison of the diameters of the tumours in the anti-NC-I.I-treated mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…A study by Ferrin et al [23] reported that the numbers of NK cells in patients with tumors were lower than those in healthy people, resulting from the consumption of tumor cells and precursors of NK cells that did not differentiate to maturity. Others have suggested that NK cells could not play the role of immunosurveillance and kill tumor cells because the activity of NK cells in cancer patients was depressed [24]. An increased number of cells may not indicate an intensification of immunity.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ferrin et al [23] reported that the numbers of NK cells in patients with tumors were lower than those in healthy people, resulting from the consumption of tumor cells and precursors of NK cells that did not differentiate to maturity. Others have suggested that NK cells could not play the role of immunosurveillance and kill tumor cells because the activity of NK cells in cancer patients was depressed [24]. An increased number of cells may not indicate an intensification of immunity.…”
Section: Discussionmentioning
confidence: 99%
“…When this tumour was transplanted into C57BLi6 mice pre-treated with 2B6-F2, a significant increase in the B16 growth rate was observed. Smart et al (1992) have previously reported that lysis of B16 in vitro was almost completely mediated by NK-1.1+ cells. Evidence for the involvement of NK-1.1+ cells in immunosurveillance against B16 local tumour growth and metastasis in vivo has been provided by studies performed in normal mice depleted of NK-1.1+ cells with MAb PK136 (Seaman et aL, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that C57BL/6 splenic NK-1.1+ cells kill the NK-sensitive tumour cell lines YAC-1 and B16 melanoma in 18-hr 51Cr-release assays (Smart et al, 1992). NK-1.1+ cells have also been shown to mediate immune surveillance against local growth and metastasis of the B16 melanoma in vivo (Seaman et al, 1987).…”
mentioning
confidence: 99%
See 2 more Smart Citations